Visual communication in practice: A texto-material approach to WhatsApp in Mexico City - Gómez Cruz, Edgar (2021)
With more than 2 billion users, WhatsApp is one of the most important mobile technologies in the world. Accordingly, scholarly interest in WhatsApp has grown in recent years. However, studies have tended to separate WhatsApp’s visual and textual elements from the analysis of its technological infrastructure. Alternatively, we argue for a “texto- material” approach that examines the links between both dimensions. We elaborate on the analytical gains that come from this approach by examining the use of WhatsApp in Mexico City. We posit that considering how textual/visual elements and technological features are interwoven is crucial for understanding the cultural specificity of WhatsApp’s development and use in places like Latin America.